2023
DOI: 10.22541/au.167338513.35935613/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downstream signaling of disease-associated mutations on GPR56/ADGRG1

Abstract: GPR56/ADGRG1 is an adhesion GPCR and mutations on this receptor cause cortical malformation due to the over-migration of neural progenitor cells on the brain surface. At the pial surface, GPR56 interacts with collagen III, induces Rho dependent activation through Gα12/13 and inhibits the neuronal migration. In human glioma cells, GPR56 inhibits cell migration through Gαq/11 dependent Rho pathway. GPR56-tetraspanin complex is known to couple with Gαq/11. GPR56 is an aGPCR that couples with various G proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…2A, Fig. S1) [73]. Autoproteolysis‐deficient ADGRG1H381S constructs were resolved on SDS‐PAGE as higher bands corresponding to their molecular weights using anti‐GPR56 antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A, Fig. S1) [73]. Autoproteolysis‐deficient ADGRG1H381S constructs were resolved on SDS‐PAGE as higher bands corresponding to their molecular weights using anti‐GPR56 antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The stronger activation of GPR56-CTF with P19 is in line with previous work by Stoveken and colleagues that showed a roughly 1.5-fold increase of P19 stimulation over P7 stimulation for the related GPR56 A386M CTF construct. 35 While GPR56-FL was lacking the ability to be activated on membranes using P7 in GTPγS binding assays, other studies have reported signalling activation of GPR56-FL by the P7 peptide in BRET-based assays in HEK293 cells, 66 and activation of Ca 2+ signalling in MIN6 mouse pancreatic beta cells. 67 Additionally, murine GPR56-FL could be activated by the GPR56/GPR114 peptide ligand P19, 68 and administration of P7 or P19 resulted in GPR56-mediated antidepressant-like effects in mice and upregulated related signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thorough signalling profiling requires assays that cover the full panel of G protein signalling pathways, which previously has been challenging for receptors coupled to the G12/13 pathway due to a lack of efficient and pathway‐specific downstream assays. In this issue, Faas et al (Rosenkilde group) 23 describe a new strategy for detecting ADGRG1 G12/13 signalling, which nicely complement the BRET strategies laid forward by Cevheroğlu et al 22 and Ojeda‐Muñiz et al 21 Using chimeric G proteins, Faas and co‐workers reroute GPR56 G12/13 signalling activity to a convenient Gq readout and show that synthetic Stachel peptide ligands in combination with these chimeras enhance the signalling in conventional gene transcription factor and second messenger assays. As such, the authors offer an additional readout for signalling profiling of adhesion GPCRs in the G12/13 pathway.…”
mentioning
confidence: 95%
“…ADGRG1 (GPR56) is associated with the monogenetic disease bilateral frontoparietal polymicrogyria (BFPP) as well as cancer and represent a potential promising drug target. Cevheroğlu et al (Son Group) 22 utilize synthetic Stachel peptide activation and BRET biosensors to investigate the effect of BFPP disease associated mutations on ADGRG1 signalling. The authors investigate the peptide‐dependent activation of G proteins and β‐arrestin membrane recruitment.…”
mentioning
confidence: 99%